2014
DOI: 10.1002/2014jb011139
|View full text |Cite
|
Sign up to set email alerts
|

Sheared sheet intrusions as mechanism for lateral flank displacement on basaltic volcanoes: Applications to Réunion Island volcanoes

Abstract: Field work carried out on the Piton des Neiges volcano (Réunion Island) suggests that the injection of magma along detachments could trigger flank failure by conjugate opening and shear displacement. We use 3-D numerical models to compare the ability of purely opened sheet intrusions, sheared sheet intrusions, and normal faults to induce flank displacement on basaltic volcanoes. We assume that shear stress change on fractures results from stress anisotropy of the host rock under gravity. Exploring a large ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 93 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Thus, the rake is fixed at 90°based on the eastward GPS displacement recorded between 2 and 10 April at the only station (FERg) located to the east of the summit [Peltier et al, 2009a]. We also use a modified computation where fracture interpenetration is not permitted, a condition enforced through the use of Lagrange multipliers as explained in Cayol et al [2014]…”
Section: Inverse Modeling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the rake is fixed at 90°based on the eastward GPS displacement recorded between 2 and 10 April at the only station (FERg) located to the east of the summit [Peltier et al, 2009a]. We also use a modified computation where fracture interpenetration is not permitted, a condition enforced through the use of Lagrange multipliers as explained in Cayol et al [2014]…”
Section: Inverse Modeling Methodsmentioning
confidence: 99%
“…Because we questioned whether the obtained closure was really required to explain the surface displacement, inversions preventing fracture interpenetration were also conducted [Cayol et al, 2014]. A demonstrably less good fit was obtained (RMSE = 3.52 and AIC = 2889, inversion termed "No interp" in Table 4), which indicates that closure of the fracture is the most likely model.…”
Section: Nonlinear Inversion Of Geometry Location and Homogeneous Smentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the role of sheared sill intrusions as a trigger of flank instability has been tested numerically. Using the observed geometry of the Piton des Neiges sill zone, Cayol et al (2014) computed that the injection of sills in a volcanic edifice undergoing extension would generate an averaged shear displacement of 3.7 m per sill, or a total lateral displacement of 180-260 m for the sill zone. In addition, (Chaput et al, 2014a) showed that the injection of a sill could be sufficient to activate a detachment such as the one found at Piton des Neiges.…”
Section: Implication For the Role Of Sill Intrusions In Volcano Flankmentioning
confidence: 99%
“…Each sill would activate slip on the detachment, progressively increasing flank instability and eventually leading to flank failure. This model has been tested by numerical simulations, which show that sill intrusions in a volcanic edifice under extension may indeed yield lateral flank displacements, and may also activate a pre-existing detachment (Cayol et al, 2014;Chaput et al, 2014a). However, there is to date no observational constraints that sill intrusions cause a shear displacement during their emplacement.…”
Section: Introductionmentioning
confidence: 99%